Evidence of a Role for Fibroblast Transient Receptor Potential Canonical 3 Ca2+ Channel in Renal Fibrosis. - Youakim, Saliba (2014)
Transient receptor potential canonical (TRPC) Ca2+-permeant channels, especially TRPC3, are increasinglyimplicated in cardiorenal diseases. We studied the possible role offibroblast TRPC3 in the development ofrenalfibrosis.In vitro, a macromolecular complex formed by TRPC1/TRPC3/TRPC6 existed in isolatedcultured rat renalfibroblasts. However, specific blockade of TRPC3 with the pharmacologic inhibitor pyr3was sufficient to inhibit both angiotensin II- and 1-oleoyl-2-acetyl-sn-glycerol–induced Ca2+entry in thesecells, which was detected by fura-2 Ca2+imaging. TRPC3 blockade or Ca2+removal inhibitedfibroblastproliferation and myofibroblast differentiation by suppressing the phosphorylation of extracellular signal-regulated kinase (ERK1/2). In addition, pyr3 inhibitedfibrosis and inflammation-associated markers in anoncytotoxic manner. Furthermore, TRPC3 knockdown by siRNA confirmed these pharmacologicfind-ings. In adult male Wistar rats or wild-type mice subjected to unilateral ureteral obstruction, TRPC3 ex-pression increased in thefibroblasts of obstructed kidneys and was associated with increased Ca2+entry,ERK1/2 phosphorylation, andfibroblast proliferation. Both TRPC3 blockade in rats and TRPC3 knockout inmice inhibited ERK1/2 phosphorylation andfibroblast activation as well as myofibroblast differentiationand extracellular matrix remodeling in obstructed kidneys, thus ameliorating tubulointerstitial damageand renalfibrosis. In conclusion, TRPC3 channels are present in renalfibroblasts and controlfibroblastproliferation, differentiation, and activation through Ca2+-mediated ERK signaling. TRPC3 channels mightconstitute important therapeutic targets for improving renal remodeling in kidney disease.